#### Answer

$18$

#### Work Step by Step

$(\sqrt 2 + 4i)(\sqrt 2 - 4i) = 2 +4i\sqrt 2 - 4i\sqrt 2 - 16i^2 = 2 -16 (-1) = 18$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$18$

$(\sqrt 2 + 4i)(\sqrt 2 - 4i) = 2 +4i\sqrt 2 - 4i\sqrt 2 - 16i^2 = 2 -16 (-1) = 18$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.